A REVIEW OF UNIDIRECTIONAL LINK IN MULTIHOP MANETs (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
Mobile ad hoc networks [MANETs] are a set of mobile nodes that are communicating with one another via wireless links without having any existing infrastructure. MANETs pose many challenges in terms of routing, due to their mobile nature of nodes, fixed transmission power and constantly changing topologies. A node in a MANET may not directly reach every other node, it is possible that the packet from source to destination may need to follow a multiple wireless links. As a result, the links might affect, and a unidirectional link can incur in MANETs.The capacity of network can be reduced due to the ignorance of unidirectional links and it can also lead towards network portioning. The concerns of such types are very much relevant to MANETs, where the transmission power and bandwidth are limited, and the links are not necessarily always bidirectional. In this paper, many protocols are reviewed for the problem of unidirectional/asymmetric links in MANETs.